Frontiers of fracture and fatigue: Some recent applications of the local strain energy density (Fracture and Structural Integrity, 2017)
The phenomenon of brittle fracture occurs too often in various branches of engineering being the reason of unexpected termination of anticipated service lives of an engineering objects. This leads to unfortunate catastrophic structural failures resulting in loss of lives and in excessive costs. The theory of fracture mechanics enables the analysis of brittle and fatigue fracture and helps to prevent the occurrence of brittle failure. This field has engaged researchers from various fields of engineering from the early days until today. As its own scientific discipline, it is now less than fifty years old and encourages scientists and engineers to speak the same language when dealing with the design and manufacturing of the classical machinery as well as various intricate devices of nanometer scale, or even smaller, reasoning significant scale effects that arise. Attempting to strike a common ground will connect various physical events/phenomena as a natural result of curiosity arising in course of joint research activities. The interpretation provided by the strain energy density to face different problems and applications is presented in this paper considering some recent outcomes at different scale levels.
Keywords: Strain energy density; Control radius; Finite size volume; Multiscale; Additive materials